Climate and culture in Australia and New Zealand - Cranston, CA; Dawson, C (Cambridge University Press, 2017)
Like a template for a climate-changing world, Australia - the driest inhabited continent on Earth - exists in an imaginative and emotional landscape shaped from extremities. Situated within the geopolitical region of Australasia/Oceania, Australia's trans-Tasman relations with earthquake-prone Aotearoa (''land of the long white cloud'') began in 1788 when New Zealand was included within the British colony of New South Wales. New Zealand, however, was never a penal colony and separation from its rough cousin came after Maori (consolidated under a single language) signed the Treaty of Waitangi with the British Crown in 1840 - itself a marker of difference between the First Nations of both countries. Australian Aborigines, scattered across the continent, each nation speaking its own language - saw land rights withheld under the illegal fiction of terra nullius , ''nobody's land."